Pelatihan Komunikasi Keluarga untuk Mengelola Stres di Masa Pandemi COVID-19 dan Menjadi Pribadi Tangguh: Lembaga Kesejahteraan Sosial Pundi Rakyat Jakarta - Meilani Dhamayanti; Siti Dewi Sri Ratna Sari; Donant Alananto Iskandar (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2022)
The COVID-19 pandemic in Indonesia has been going on for almost two years. In addition to having an impact on the people's economy, this prolonged pandemic has also disrupted the mental health of the society so that it requires good resilience to recover. This training activity aims to provide knowledge about family communication to manage stress during the COVID-19 pandemic for mothers organized by Pundi Rakyat Jakarta Social Welfare Institution in order to make them tough individuals. The method used in this activity is in the form of online training through Google Meet application with a duration of two hours which was held on Sunday, November 28, 2021. The training activities carried out for the participants were material explanations and case studies, followed by questions and answers session and sharing experience on family communication implementation. The participants were able to take part in the training well and begin to understand family communication to manage stress to become tough individuals.